The Possibility of Addressing Mandatory Rules and Its Adjustments in the Framework of International Commercial Arbitration - Al Fatayri, Layan (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
Mandatory rules are rules that apply to disregard the law chosen by the parties in their agreement. In this article, we will examine and address the role of international commercial arbitration and arbitrators when facing issues related to mandatory rules. It should be stated that mandatory rules pose conflicts for arbitrators because they place the state’s and the parties’ interests in competition. This highlights the main issue of whether the arbitrator should apply the related law when the parties’ agreement does not include this law. In other words, what should the arbitrator do in this case? The answer to this issue varies due to the variety of ways in which the “nature of arbitration” might be legally interpreted. However, a practical solution is needed. In order to reach a practical solution, the author will assess, from a normative approach, the relative benefits of various methodological techniques and their adjustments that are now in use. Then finally, conclusions will be reached regarding the approach and methodological techniques that best balance the parties' interests.